ASESSING DEVELOPMENT VALUE CREATION PT MRT JAKARTA IN MANAGING TRANSIT ORIENTED USING STRATEGIC ASSUMPTION AND TESTING AND INTERPRETATIVE STRUCTURAL MODELLING - Ardiansyah, Zulfadli; Marimin, Marimin; Indrawan, Dikky; Yurianto, Yurianto (International Journal of Business Studies, 2025)
This study aims to conduct an analysis environment business and find out the elements that play the most important role in assessing the development of value creation at PT MRT Jakarta for the creation of TOD. The expert team will identify, assess, and map various strategic assumptions that appear in the SAST strategic assumption quadrant diagram and Interpretative Structural Modeling. The assessment of each expert from the experts will be taken as a team assessment by determining the statistical mode for each factor for each category. The most important elements are the commitment of government leaders in the development of KBT, associations, regulations that are not yet synchronized, clear authority in the development and management of KBT, completeness of related regulations, the DKI provincial government's support in the use of BMD. Integrated Planning Policy: To create a successful transit-based area, a policy is needed that integrates transportation planning with spatial planning. The local government and PT MRT must work together to develop a plan that considers aspects of land use, transportation, and public services.